STRATEGI PENGEMBANGAN TABUNGAN DENGAN PENDEKATAN BUSINESS MODEL CANVAS PADA BANK SYARIAH INDONESIA - Nurul Setianingrum; Indah Dwi Lestari; MF Hidayatullah; Angrum Pratiwi (Indonesian Scientific Journal of Islamic Finance, 2023)
The business and technological environment is experiencing changes in use, influencing the current macro and micro economic environment. Changes in consumer behavior and competition in all sectors require companies to compete and maintain their business. Companies need to focus on customer satisfaction in addition to sales and profits. Satisfied customers create loyalty and profits. The research focuses on implementing the Easy Mudharabah Savings development strategy using the Business Model Canvas. The aim is to understand the Business Model Canvas that can be applied to BSI Easy Mudharabah Savings and the implications of its development strategy. This type of research is descriptive with a qualitative approach. The location of this research is PT. Indonesian Sharia Bank. Data was collected through observation, interviews, documentation and triangulation. Data analysis includes data collection, data reduction, data presentation, and drawing conclusions. The results of this research show: 1) BSI's value proposition is low admin costs, e-channel facilities, and profit sharing. 2) Customer segment is the target customer for Easy Mudharabah Savings. 3) Communication channels with customers through websites and personal selling. 4) Customer relationships are carried out through friendly service from BSI employees. 5) Revenue stream comes from admin fees and profit sharing. 6) Key partners are BSI employees. 7) Key activities include marketing and creating an Easy Mudharabah Savings account. 8) Key resources are BSI and E-channel employees. 9) Cost structure includes promotional and operational costs in marketing activities.